Support for free-market policies and reforms: Does the field of study influence students' political attitudes? - Mira Fischer; Björn Kauder; Niklas Potrafke; Heinrich W. Ursprung (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2016)
Since opinion leaders are usually university graduates, the field of study has an influence on public support for economic policies and policy reforms intended to enhance efficiency because advocating such policies often requires appreciation of the beneficial roles of markets and economic freedom. We investigate whether the field of study influences German university students' political attitudes. We disentangle self-selection from learning effects and reveal systematic differences between incoming students' political attitudes across eight fields of study. In a second step we explore how the students' political attitudes change as they progress in their academic training. Only studying economics has an unambiguous pro-market influence on political attitudes: by the time of graduation, economics students are some 6.2 percentage points more likely than they were in their initial year of study to agree with free-market policy positions. Studying humanities and natural sciences has a pro-leftist influence.
Keywords: A13; A22; B40; D01; Z13; 330; Indoctrination; nature versus nurture; political socialization; political attitudes